Automated Dirt and Stain Removal Using Soapless Ultrasonic Dishwasher - C. Cordova, Albino; C. Dizon, Joshua; Joseph S. Sia, Emmanuel; Anne, Stephanie; P. Arada, Gerald; C. Abad, Alexander; Magsino, Elmer (International Journal of Engineering and Technology, 2018)
Dishwashers are starting to become a common sight in households. Due to this fact, there will also be a rise in the demand for soap for dishwashing. An increase in the demand for soap will therefore increase the volume of wastewater produced in each of the current households. Using dishwashing liquid also poses environmental threat. This paper addressed those issues by constructing an automated soapless ultrasonic dishwasher prototype. It was developed using piezoelectric transducers which are set at 28 kHz to maximize the cleaning range. The ultrasonic generator produces waves at 28 kHz to turn on the transducers. The transducers then produce the vibrations which start the ultrasonic cavitation process. The ultrasonic cavitation process is the one mainly responsible for cleaning. The microscopic bubbles produced strike the utensils and subsequently remove dirt and stains. Furthermore, the ultrasonic dishwashing system has a solenoid and ball valve connected to it in order to facilitate automated filling up and draining of water. Tests were carried out to determine the effectivity of the constructed ultrasonic dishwasher prototype which involve subjecting pans, plates and drinking glass to different types of stains to ultrasonic energy. Finally, the optimum time of removal of dirt and stains for a specific type of stain on a specific type of material of the dish wares have been determined.
Keywords: ultrasonic; cavitation; cleaning tank; piezoelectric transducer; ultrasonic dishwasher; ultrasonic generator